Using Story Mapping Technique to Improve Students’ Ability in Writing Recount Text - Rizka Yunda; Endang Komariah; Burhansyah Burhansyah (Universitas Syiah Kuala, 2017)
This study aims at examining whether or not the use of story mapping technique can improve students’ ability in writing recount text. It was conducted to the second grade of SMPN 1 Darul Imarah. The sample was chosen randomly. There were 25 students as the sample. Quantitative approach with pre-experimental type of one group pre-test post-test design was undertaken to overcome the problems faced by students in learning writing skill. The data was obtained by giving a set of tests in the form of written test. Some statistical formulas were used to analyse the data. From the results of the study, it reveals that the post-test score of five aspects in writing is higher than the score of pre-test. To test the hypothesis, the writer used t-score formula. Based on data analysis, t-score was 21.03, meanwhile t-table was 2.064. It means that t-score was higher, so that alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. It proves there is a significant improvement on the students’ writing ability after they are taught by using story mapping technique. Thus, story mapping can be one of the alternative techniques used by the teacher in teaching writing.